Treatment of Trophic Ulcers in Patients With Chronic Venous Insufficiency Using Phototherapy and Synthetic Wound Coverings - Yu. V. Ivanova; V. A. Prasol; K. V. Miasoiedov; L. M. Al Kanash (Transplantation and artificial organs, 2020)
The aim of the study was to improve the results of treatment in patients with chronic venous insufficiency with trophic ulcers due to the use of artificial wound dressings and platelet-rich growth factors. The study included 34 patients who had trophic ulcers on the skin of the lower leg (n/3 and c/3). Group I (comparisons) included 11 (32.4%) patients who received conventional treatment; in the second group - 23 (67.6%) patients who underwentcomprehensive treatment according to the method developed by us.The criteria for the study was the presence of trophic ulcers of the leg, which were unhealed for a long time; the presence of posttroflebitic disease; preserved pulsation on the arteries of the limbs. Patients were treated with trophic ulcers by phototherapy, by scleroobliteration of insolvent perforant,and by closing the wound defect with a synthetic wound cover. In all patients of the main group, the treatment time did not exceed 39 days. In the comparison group, this indicator ranged from 28 to 53 days (depending on the area of wounds and the characteristics of thecourse of the wound process).